Isolation and characterization of endophytic bacteria from the vegetative phase of Indonesian garlic cv. ‘Tawangmangu Baru’ - Saptini Mukti Rahajeng,; Farida Yulianti,; Unun Triasih,; Dita Agisimanto,; Nirmala F. Devy,; Hardiyanto,; Nur Hayati Hadiba,; Hadi M. Yusuf, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The high demand for garlic (Allium sativum L.) has led to efforts to improve its productivity. Garlic endophytic bacteria have been found to boost the growth of garlic plants and protect them from diseases without any harmful effects on the host. The objective of the study was to isolate and characterise the endophytic bacteria present in the healthy local Indonesian garlic cv. ‘Tawangmangu Baru’ towards developing them as plant growth-promoting bacteria in improving garlic quality and productivity. The isolation of endophytic bacteria was performed from garlic leaves and roots during the vegetative phase. A total of 20 endophytic bacteria isolated from garlic leaves and roots were characterised by their morphology and tested for their ability to fix nitrogen (N), produce auxin (IAA), and solubilise phosphate. All the isolates were able to fix nitrogen, with 15 of the isolates found to be Gram-positive having bacilli cell shape. Furthermore, 8 isolates were shown to produce auxin, while 10 isolates were able to solubilise phosphate, with both groups originating from the root sample. Five potential isolates were identified as nitrogen-fixing, IAA-producing, and phosphate-solubilising, with the highest values of IAA concentration and the Phosphate Solubilisation Index (PSI) being 10.71 ppm and 2.00, respectively. These 5 potential endophytic bacterial isolates were genetically identified as similar to Lysobacter tolerans, Enterobacter cloacae, Enterobacter huaxiensis, Klebsiella oxytoca, and Enterobacter hormaechei. The potential endophytic bacterial isolates hold promise for developing garlic plant growth-promoting bacteria (PGPB) to enhance garlic production both qualitatively and quantitatively.